2015
DOI: 10.1364/boe.6.001738
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of imaging with extended depth-of-field by means of the light sword lens in terms of visual acuity scale

Abstract: Abstract:We present outcomes of an imaging experiment using the refractive light sword lens (LSL) as a contact lens in an optical system that serves as a simplified model of the presbyopic eye. The results show that the LSL produces significant improvements in visual acuity of the simplified presbyopic eye model over a wide range of defocus. Therefore, this element can be an interesting alternative for the multifocal contact and intraocular lenses currently used in ophthalmology. The second part of the article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 30 publications
2
33
0
2
Order By: Relevance
“…Performance of the LSL as a corrector element was evaluated recently by means of objective experiments using a simplified model of a presbyopic eye. 24 The results demonstrated that the LSL in a contact lens configuration significantly improves the visual acuity (VA) of a monofocal optical system within a wide range of defocus. Results from the objective experiments and numerical simulations 22,23 showed that the performance of the LSL is superior to other available solutions.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Performance of the LSL as a corrector element was evaluated recently by means of objective experiments using a simplified model of a presbyopic eye. 24 The results demonstrated that the LSL in a contact lens configuration significantly improves the visual acuity (VA) of a monofocal optical system within a wide range of defocus. Results from the objective experiments and numerical simulations 22,23 showed that the performance of the LSL is superior to other available solutions.…”
mentioning
confidence: 95%
“…These optical elements include axicons with an axial symmetry profile 17 and some structures with an asymmetrical profile such as the cubic phase mask, 18 the peacock eye optical element, 19 and the light sword lens (LSL). 20 Previous studies have proposed use of the LSL to correct presbyopia [20][21][22][23][24] because it was designed to image objects at a wide range of distances. Performance of the LSL as a corrector element was evaluated recently by means of objective experiments using a simplified model of a presbyopic eye.…”
mentioning
confidence: 99%
“…Desde Polonia, los profesores Zbigniew Jaroszewicz y Andrzej Kolodziejczyk del instituto de Óptica Aplicada de Varsovia y la Universidad Tecnológica de Varsovia, han dejado un legado importante en el estudio de elementos difractivos diseñados para el mejoramiento del sistema visual humano (Kakarenko, et al, 2015). Así mismo, sus enseñanzas han marcado el desarrollo de grupos de estudio de la luz como el de la Universidad de Antioquia.…”
Section: Nuestros Formadoresunclassified
“…Grupos consolidados de investigación en las Universidades de Antioquia, Eafit, ITM, Medellín, Nacional de Colombia Sede Medellín, Politécnico Jaime Isaza Cadavid y Pontificia Bolivariana, constituyen el núcleo más sólido para el estudio de la luz en Colombia. La región cuenta en la actualidad con grupos de investigación es este campo con la máxima categoría otorgada por la rectora de la investigación en Colombia Colciencias, trabajando en temas como óptica visual (Kakarenko, et al, 2015), teoría de coherencia (Castañeda, 2014) El sueño de aquellos que iniciaron el estudio de la luz en Antioquia se ha hecho realidad. Varios grupos de la región son referentes internacionales en su dominio de conocimiento.…”
Section: El Estudio De La Luz Se Mantiene Hasta Nuestros Díasunclassified
“…[5][6][7][8][9][10][11][12][13][14][15][16] Nevertheless, it has been shown that cubic and trefoil-shaped phases are most used to achieve high-quality images when spherical aberration, 10,11) astigmatism 14,15) and high orderaberrations 15) are also present in the system. WFC can be found in many different applications such as in ophthalmic optics, [15][16][17] iris recognition, 18,19) complexity reduction in optical systems, 20) control of thermal defocus in infrared systems, 21) barcode reading, 22) and microscopy, 23) among many others. The DOF in each application can be extended by a trefoil phase at the exit pupil of the optical system, and the trade-off between the DOF and the image resolution properties is dependent on the peak-to-valley value (strength) of the phase.…”
Section: Introductionmentioning
confidence: 99%